Knowledge Management in Sericulture Cultivation and Weaving of Natural Dyed Silk of the Community Enterprise Group in Phon District, Khon Kaen Province - Aeknanrajindawat, Natnaporn (Rajapark Journal, 2023)
The objectives of this research were to study 1) the knowledge management in sericulture cultivation and weaving of natural dyed silk; 2) the potential of communities in silk weaving, dyeing and natural dyeing; 3) the establishment of a knowledge center on silk weaving; 4) the network of silk weaving community enterprises; and 5) plan the development of cultural tourism in the silk weaving community. This research employed mixed method research. In the qualitative research part, in-depth interviews with 13 people related to the learning center of sericulture cultivation and weaving of natural dyed silk were purposive selecting. In the quantitative research part, the sample consisted of community enterprise groups and entrepreneurs of sericulture cultivation or silk weaving, the local people, consumers, and tourists amounting to 400 people by using a simple random sampling method. Data were collected via a questionnaire and analyzed with a descriptive statistic. The research findings showed that: 1) the knowledge management in sericulture cultivation and weaving of natural dyed silk. The overall picture was at a high level. 2) the potential of communities in silk weaving. The overall picture was at a high level. 3) 3 main knowledge management processes: 1. knowledge acquisition and creation, 2. knowledge transfer and exchange, and 3. utilization and application of knowledge. 4) the network of silk weaving community enterprises. The overall picture was at a highest level. 5) plan the development of cultural tourism in the silk weaving community. The overall picture was at a high level. Qualitative research results: community enterprise groups should develop techniques for growing sericulture cultivation in order to obtain quality produce and should develop the silk weaving process to support the world market